2019
DOI: 10.1093/neuonc/noz118
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in newly diagnosed glioma patients: which symptom clusters are independently associated with functioning and global health status?

Abstract: BackgroundSymptom management in glioma patients remains challenging, as patients suffer from various concurrently occurring symptoms. This study aimed to identify symptom clusters and examine the association between these symptom clusters and patients’ functioning.MethodsData of the CODAGLIO project was used, including individual patient data from previously published international randomized controlled trials (RCTs) in glioma patients. Symptom prevalence and level of functioning were assessed with European Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Our study demonstrated the postoperative long-term independence status varied considerably across meningioma patients, especially patients with preoperative KPS equal to 80 and 70 have obvious polarization trends in postoperative long-term independence. Then, similar to what has been reported in a previous study about glioma (30), we have found that fatigue, memory impairment, motor dysfunction, and communication deficits were consistently highly correlated with long-term loss of independence in elderly meningioma patients. Finally, we identified several independent risk factors to develop and internally validate a prediction model for postoperative long-term loss of independence in the elderly with meningioma.…”
Section: Discussionsupporting
confidence: 90%
“…Our study demonstrated the postoperative long-term independence status varied considerably across meningioma patients, especially patients with preoperative KPS equal to 80 and 70 have obvious polarization trends in postoperative long-term independence. Then, similar to what has been reported in a previous study about glioma (30), we have found that fatigue, memory impairment, motor dysfunction, and communication deficits were consistently highly correlated with long-term loss of independence in elderly meningioma patients. Finally, we identified several independent risk factors to develop and internally validate a prediction model for postoperative long-term loss of independence in the elderly with meningioma.…”
Section: Discussionsupporting
confidence: 90%
“…For example, one study found that 89% of patients with PBT who were categorized as having insomnia endorsed fatigue [ 31 , 33 ]. These findings are clinically relevant given that fatigue is known to adversely affect both the quality of life (e.g., disrupting mood) and functioning of PBT patients [ 34 , 35 ]. Similarly, the association between corticosteroids use and sleep disturbance has been shown in previous investigations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between these different disciplines, a leadership role for patients and caregivers is needed to ensure fixed contact partners and a managing/coordinating department. Especially patients with primary brain tumors as well as their caregivers might need a designated site for contact due to the high amount of psycho-social distress and impairment in physical and cognitive functioning [28]. Neuro-oncological neurologists, as representatives of a non-interventional discipline, may be predisposed to this role.…”
Section: Value and Relevance Of Ntbsmentioning
confidence: 99%